Relationship between trait anxiety and stress coping styles in offending drivers in Metropolitan Lima - Briozo A., Marco (2015)
This research is quantitative, descriptive and correlational type whose principal aim is to find the correlation between trait anxiety and coping styles to stress in offending drivers in Metropolitan Lima. For this purpose, the State-Trait Anxiety Inventory (STAI) and Stress Coping Styles Test by Cope will be used. Under an intentional sampling and a non-experimental study, it aims to find a significant correlation and the most predominant levels of coping styles. The research findings show a direct correlation between Trait Anxiety and the styles of Planning Activities, Analysis of Emotions, Negation and Inappropriate Behavior. On the other hand, it shows inverse correlation between Trait Anxiety and the styles of Search of Social Support, Search of Emotional Support, Competitive Activities Suppression, Positive Reinterpretation of Experience, Acceptance and Distraction. Finally, there is no correlation between stress coping strategies and Direct Coping, Coping Retraction and Return to Religion.